Survey of Human Oxidoreductases and Cytochrome P450 Enzymes Involved in the Metabolism of Xenobiotic and Natural Chemicals - Rendic, Slobodan (Chem Res Toxicol, 2014)
[Image: see text] Analyzing the literature resources used in our previous reports, we calculated the fractions of the oxidoreductase enzymes FMO (microsomal flavin-containing monooxygenase), AKR (aldo-keto reductase), MAO (monoamine oxidase), and cytochrome P450 participating in metabolic reactions. The calculations show that the fractions of P450s involved in the metabolism of all chemicals (general chemicals, natural, and physiological compounds, and drugs) are rather consistent in the findings that >90% of enzymatic reactions are catalyzed by P450s. Regarding drug metabolism, three-fourths of the human P450 reactions can be accounted for by a set of five P450s: 1A2, 2C9, 2C19, 2D6, and 3A4, and the largest fraction of the P450 reactions is catalyzed by P450 3A enzymes. P450 3A4 participation in metabolic reactions of drugs varied from 13% for general chemicals to 27% for drugs.